Anti-inflammatory/antioxidant use in long-term maintenance cancer therapy: a new therapeutic approach to disease progression and recurrence. - Crawford, Sarah (Therapeutic advances in medical oncology, 2014)
The chronic, progressive clinical characteristics of many adult solid tumor malignancies suggest that a more effective therapeutic approach to cancer management may require long-term intervention using nontoxic systemic agents that block critical components of abnormal tumor physiology. Two highly promising systemic targets common to the development, progression and recurrence of many common cancers are dysregulated inflammatory and oxidation/reduction (redox) pathways. Compelling clinical data support the use of anti-inflammatory and antioxidant agents as a therapeutic modality for long-term use in patients diagnosed with several common cancers, including colon cancer and breast cancer. The therapeutic paradigm presented in this paper is the product of a synthesis of what is currently understood about the biological effects of inflammation and oxidative stress that contribute to tumorigenesis, disease progression and recurrence as well as results obtained from research on the use of prophylactics with anti-inflammatory or antioxidant properties in cancer prevention and treatment.
Keywords: anti-inflammatory agents; antiinflammatory agent; antioxidant; antioxidants; axitinib; bevacizumab; bosutinib; breast cancer; cabozantinib; cancer epidemiology; cancer growth; cancer recurrence; cancer therapy; cetuximab; chemoprophylaxis; chemotherapy; colon cancer; crizotinib; dasatinib; dept.bio; erlotinib; everolimus; gefitinib; human; imatinib; inflammation; ipilimumab; lapatinib; long term care; long-term maintenance cancer therapy; meta analysis (topic); nilotinib; nonhuman; oxidative stress; panitumumab; pazopanib; ponatinib; priority journal; randomized controlled trial (topic); reactive oxygen metabolite; regorafenib; review; ruxolitinib; sorafenib; sunitinib; systematic review (topic); temsirolimus; tofacitinib; trastuzumab; trastuzumab emtansine; unindexed drug; vandetanib; vemurafenib